Study of skimming flow in flat slope stepped channels (2017)
In this thesis, the results of a numerical modeling study that addresses the skimming flow properties in flat slope stepped channels, are presented and analyzed. Experimental data of mean flow velocity profiles from Hunt and Kadavy's physical model was used for the calibration of the results obtained with a numerical model performed with the commercial CFD tool: Ansys Fluent. SST k-omega was selected for turbulence modeling and Mixture model for the free surface tracking process, but as the flow aeration downstream the inception point wasn't captured by the mentioned models, a "data adjustment procedure" was proposed to be able to compare the experimental data from measuring stations with air entrance, with the numerical results. This work presents a hydrodynamical diagnosis addressing the relations between the mean flow velocity, static pressure, turbulent kinetic energy production and viscous dissipation rates along the skimming flow domain. Additional runs with wall roughness, riser height (h) and tread length (l) variations were performed to conclude about the effects in the mentioned hydrodynamical variables.